From content distribution networks to content networks — issues and challenges - Plagemann, Thomas; Goebel, Vera; Mauthe, Andreas; Mathy, Laurent; Turletti, Thierry; Urvoy-Keller, Guillaume (Computer communications, 2006)
Due to the technical developments in electronics the amount of digital content is continuously increasing. In order to make digital content respectively multimedia content available to potentially large and geographically distributed consumer populations, Content Distribution Networks (CDNs) are used. The main task of current CDNs is the efficient delivery and increased availability of content to the consumer. This area has been subject to research for several years. Modern CDN solutions aim to additionally automate the CDN management. Furthermore, modern applications do not just perform retrieval or access operations on content, but also create content, modify content, actively place content at appropriate locations of the infrastructure, etc. If these operations are also supported by the distribution infrastructure, we call the infrastructure Content Networks (CN) instead of CDN. In order to solve the major challenges of future CNs, researchers from different communities have to collaborate, based on a common terminology. It is the aim of this paper, to contribute to such a terminology, to summarize the state-of-the-art, and to highlight and discuss some grand challenges for CNs that we have identified. Our conception of these challenges is supported by the answers to a questionnaire we received from many leading European research groups in the field.